Moore filters at Dow Chemical Company plant - Dow Chemical Company (1950)
General view of Moore filters used to process magnesium hydrate at the Dow Chemical Company's plant located in Freeport, Texas.
Keywords: Magnesium; Industries; Dow Chemical Company; Filters and filtration